2015
DOI: 10.3748/wjg.v21.i23.7248
|View full text |Cite
|
Sign up to set email alerts
|

Living donor liver transplantation with body-weight more or less than 10 kilograms

Abstract: AIM:To compare the outcomes of pediatric patients weighing less than or more than 10 kg who underwent liver transplantation. METHODS: Data for 196 pediatric patients who underwent living donor liver transplantation betweenJune 1994 and February 2011 were reviewed retrospectively. The information for each patient was anonymized and de-identified before analysis. The data included information regarding the pre-transplant conditions, intraoperative fluid replacement and outcomes for each patient. The 196 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…The mean weight of the transplanted children in this cohort was below 10 kg, a population that presents technical difficulties in vascular reconstruction during liver transplantation, as well as in perioperative care, as pointed out by some authors 17,18 . In the present study, as shown in Table 1, there was no difference in the characteristics of the recipients between the types of LLS grafts used, related to the age and weight at LT, as well as the severity of liver disease by PELD score and presence of ascites.…”
Section: Discussionsupporting
confidence: 49%
“…The mean weight of the transplanted children in this cohort was below 10 kg, a population that presents technical difficulties in vascular reconstruction during liver transplantation, as well as in perioperative care, as pointed out by some authors 17,18 . In the present study, as shown in Table 1, there was no difference in the characteristics of the recipients between the types of LLS grafts used, related to the age and weight at LT, as well as the severity of liver disease by PELD score and presence of ascites.…”
Section: Discussionsupporting
confidence: 49%
“…Subgroup analyses were performed to better understand the challenges associated with low body weight (<10 kg) of pediatric recipients and younger age at the time of transplant (<10 years old). Historically, weight above 10 kg has been predictive of graft survival and associated with improved outcomes ( 10 , 28 ). Smaller recipient size increases the technical complexity of the surgery and has been associated with higher rates of vascular and biliary complications ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LDLT allows for procurement from a healthy donor with elective scheduling of the operation and shorter cold ischemia times . Excellent patient survival, comparable to older children, is seen even in very young (<90 days old) and small (<10 kg) infants transplanted at experienced pediatric centers . A Markov model simulation found an increase of 17.45 additional expected life‐years when a LDLT was performed in a patient with a PELD of 15‐25 with 1 or fewer systemic complication as compared with those with PELD scores >25 who had more than 1 systemic complication .…”
Section: Timing Of Transplant In Biliary Atresiamentioning
confidence: 99%